2008
DOI: 10.1128/aac.00026-08
|View full text |Cite
|
Sign up to set email alerts
|

Sm qnr , a New Chromosome-Carried Quinolone Resistance Gene in Stenotrophomonas maltophilia

Abstract: A new chromosome-carried quinolone resistance gene from Stenotrophomonas maltophilia, Smqnr, was characterized. The gene was present in type strain CCUG 5866 and was also detected in 24 clinical isolates and showed some allelic diversity. The expression of Smqnr in Escherichia coli decreased the susceptibilities of the E. coli isolates to several fluoroquinolones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 13 publications
2
44
0
Order By: Relevance
“…It has been confirmed that the Smqnr gene is capable of decreasing quinolone and fluoroquinolone susceptibilities, similar to other qnr determinants (Shimizu et al, 2008). Later, a publication from Spain demonstrated the role of the Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that the Smqnr gene is capable of decreasing quinolone and fluoroquinolone susceptibilities, similar to other qnr determinants (Shimizu et al, 2008). Later, a publication from Spain demonstrated the role of the Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Smqnr28-30 were variants of Smqnr2 with identities of 96-99 %, Smqnr31-34, Smqnr40 and Smqnr47 were variants of Smqnr4 with identities of 94-99 %, and Smqnr35-38 and Smqnr41-45 were variants of Smqnr6-11 with identities of 92-99 %. The Smqnr1-11 genes were initially detected in Japan and have 2-6 amino acid residue differences in the encoded proteins compared with the qnrB gene (Shimizu et al, 2008). The Smqnr12-18 genes prevail mainly in the UK and have different amino acid residue alterations in the encoded proteins from the Smqnr1-11 genes.…”
Section: Strainmentioning
confidence: 99%
“…A gene dosage effect of SmQnr was observed when the gene was plasmid borne, in contrast to the relatively low-level expression of chromosomally carried Smqnr. The expression of the Smqnr gene has been reported to result in low-level resistance to quinolones in a heterologous host (299,313). Resistance to quinolones in S. maltophilia can occur as a result of mutations of the bacterial topoisomerase and gyrase genes (126,339) and may also arise due to the overexpression of the efflux pump SmeDEF (11,12).…”
Section: ])mentioning
confidence: 99%
“…SmQnr has two domains of 5 and 28 pentapeptide repeats separated by a glycine (179,182). An even closer homologue of qnrB has been found in DNA sequences in a marine metagenome, but its location on a bacterial chromosome or on a mobile genetic element is unknown (179).…”
Section: Chromosomal Qnr Genesmentioning
confidence: 99%